2015
DOI: 10.1002/chem.201500587
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Arylation of N‐Tosylimines by Phenylboronic Acid Catalysed by a Rhodium/Diene Complex: Reaction Mechanism from Density Functional Theory

Abstract: A DFT study of the reaction mechanism of the rhodium-catalysed enantioselective arylation of (E)-N-propylidene-4-methyl-benzenesulfonamide by phenylboronic acid [Lin et al J. Am. Chem. Soc. 2011, 133, 12394] is reported. The catalyst ([{Rh(OH)(diene)}2]) includes a chiral diene ligand and the reaction is conducted in 1,4-dioxane in the presence of drying agents (4 Å molecular sieves). Because phenylboronic acid is in equilibrium with phenylboroxin and water under the reaction conditions, three catalytic cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…The refined energies are computed with the B97‐D2 functional, that follows the DFT−D2 general approach of Grimme, in which the functional energies are corrected by an atomic pair‐wise additive term accounting for the long‐range non‐covalent interactions. B97‐D2 has been successfully employed to study Ru and Rh catalysed reactions, and has been recently shown to perform well at describing several “bulky” transition metal‐complexes …”
Section: Methodsmentioning
confidence: 99%
“…The refined energies are computed with the B97‐D2 functional, that follows the DFT−D2 general approach of Grimme, in which the functional energies are corrected by an atomic pair‐wise additive term accounting for the long‐range non‐covalent interactions. B97‐D2 has been successfully employed to study Ru and Rh catalysed reactions, and has been recently shown to perform well at describing several “bulky” transition metal‐complexes …”
Section: Methodsmentioning
confidence: 99%
“…A potential reason for deactivation might be pore blocking by Rh boronate precipitates in agreement with recent calculations of the catalytic cycle. [60]…”
Section: Molecular Heterogeneous Catalysis With Sio 2 à Io Solid Supportmentioning
confidence: 99%
“…Then, hierarchical macro-mesoporous SiO 2 À IOs were used for the first-time as a catalyst support for chiral Rh-diene complexes, and their catalytic activity and selectivity with respect to the porous material was studied. As a catalytic model reaction, the Rh-diene-catalyzed 1,2-addition of phenylboroxine to Ntosylimines was chosen, because the corresponding homogeneous catalysis has been previously studied both experimentally and theoretically [41][42][43][57][58][59][60] and thus could serve as a benchmark for our novel solid catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the much larger distance of the substituents R from the Rh center (compared with the diene ligand 140a), a high ee value was expected for the 1,4-addition products derived from aliphatic enones (Scheme 38). 99 When we used a strategy similar to that shown in Scheme 36 for the synthesis of dienes 144 from Weiss diketone 103, we noticed that, depending on the base, considerable amounts of the undesired C s -symmetrical (achiral) diene 145 were formed (Scheme 38). For example, treatment of Weiss diketone 103 with a chiral Simpkins base, trapping with triflimide, and subsequent Suzuki cross-coupling with phenylboronic acid delivered the dienes 144a and 145a in 71% yield as an 84:16 regioisomeric mixture.…”
Section: Scheme 36mentioning
confidence: 99%